Peningkatan Pengetahuan Ibu Balita Tentang Stunting Dengan Upaya Perbaikan Gizi 1000 Hari Pertama Kehidupan - Sa'danoer, Ira Maulina; Tyas, Dina Ayuning; Zaini S, Hanifa (Universitas Sumatera Barat, 2023)
Data from the Indonesian Nutrition Status Survey (SSGI), the stunting rate in West Sumatra in 2021 was 23.3%, which is below the national average. In 2022 there will be an increase from 1.9% to 25.2%, so that it is currently above the national average, namely 21.6%. Stunting prevention efforts are focused on 1000 HPK, because this period is an important period in determining the quality of life of children. This community service activity aims to help increase the knowledge of mothers of toddlers about stunting so that it can improve the nutritional status of children under five and also the knowledge gained can be disseminated by mothers of toddlers who receive the training. The method used is through brainstorming, lectures. Resource persons for this activity include the person in charge of the health center health promotion program, a team of midwifery lecturers at the University of West Sumatra. Community service activities ran well and smoothly, participants who took part in the counseling were able to explain the meaning of stunting, how to prevent stunting, signs and symptoms of stunting, and how to detect stunting. The hope is that there will be an increase in good nutritional status and reduce the incidence of stunting.